Weighted Lorentz estimate for asymptotically regular parabolic equations of p(x, t)-Laplacian type. (March 2019) - Zhang, Junjie; Cai, Maomao; Zheng, Shenzhou
Abstract: We prove a global weighted Lorentz estimate of the spatial gradients of weak solution to the Cauchy–Dirichlet problem for asymptotically regular parabolic equations of p ( x, t ) -Laplacian type in a Reifenberg flat domain. It is mainly assumed that the associated regular nonlinearity is measurable with respect to the time variable and satisfies the ( δ, R ) -vanishing condition with respect to the spatial variables.